Labor market characteristics and cultural choice. (2nd June 2020) - Ellis, Christopher; Thompson, Jon C.; Wu, Jiabin
Abstract: We develop a model of cultural selection based on the labor market characteristics of different cultural types. Following Borjas (1994, 1995) we assume that cultural heterogeneity increases labor productivity due to skill complementarities, however following Jackson and Xing (2014) we also assume that cultural heterogeneity hampers communication. We model this as a game in which individuals from two cultural types first engage in random matching, then once matched play a coordination game. Other‐type matches are thus potentially more productive, but also less likely to coordinate. We show that these two labor market characteristics serve as important primitives in determining if a cultural minority persists. Essentially, when the productivity advantages from a cross‐cultural match sufficiently outweigh the disadvantages of coordination problems then the cultural minority will persist. If not it will be assimilated. Further, we obtain results concerning the efficient size of the cultural minority, the effects of tax and welfare programs on the size and welfare of the cultural minority, and the relationship between the intensity of social interaction and size and welfare of the cultural minority.